Prevalence and Outcome of Post- thyroidectomy Hypocalcaemia: A Prospective Clinical Study - SriVignesh, M.; Arun, Alok Mohanty; Robinson, Smile R. (British Journal of Healthcare and Medical Research, 2023)
Aims: (1) To record the incidence of post-thyroidectomy hypocalcaemia. (2) To correlate blood calcium levels with symptoms of hypocalcaemia. (3) To find out the type of hypocalcaemia whether temporary or permanent. (4) To assess the risk factors for development of hypocalcaemia. Design: Prospective analysis of 50 consecutive patients undergoing thyroid surgeries. Materials & Method: All patients undergoing any thyroidectomy in the department of general surgery were followed for a period of 3 months. The type of surgery, Histopathology and clinical diagnosis to predict the outcome of post-operative hypocalcaemia was validated. The influences of Patient factors, intra-operative identification of RLN and parathyroid were also observed. Results: The overall prevalence of hypocalcaemia was 28% of which 12 patients had temporary and 2 had permanent hypocalcaemia. Only 12 patients developed clinical symptoms. Hypocalcaemia typically ensues during the early post-operative period (24-48 hrs). Hypocalcaemia was significantly associated with the type of surgery (p=0.0293), Histopathology (p=0.0312) and clinical diagnosis (p=0.0008). Age, Sex and identification of RLN and Parathyroid did not play a significant role in predicting the outcome of post-operative hypocalcaemia. Conclusion: Hypocalcaemia either transient or permanent can be debilitating and lead to significant morbidity. Temporary hypocalcaemia is common after surgery for malignancies. Histopathology, clinical diagnosis and extent of surgical resection influence the outcome of hypocalcaemia. Early measurement of serum calcium and albumin levels can ensure early management and prevent complications of hypocalcaemia.